Positive effects of ocrelizumab in patients with familial mediterranean fever and coexistent multiple sclerosis - Caner Feyzi DEMİR and Ferhat BALGETiR and Özlem ETHEMOĞLU and Dürdane AKSOY and Filiz AKTAŞ and Süleyman Serdar KOCA and Mehmet Fatih YETKIN and İrem TAŞCI (Archives of Rheumatology, 2021)
Objectives: This study aims to evaluate the effects of ocrelizumab (OCZ) on familial Mediterranean fever (FMF) attacks in multiple sclerosis (MS) patients with FMF (MS+FMF patients). Patients and methods: This retrospective observational study included 11 patients (2 males, 9 females; mean age 46.6±9.2; range, 22 to 55 years) with MS+FMF hospitalized between January 2016 and July 2019. Demographic, clinical, and laboratory parameters and patient reported outcomes were analyzed in patients treated with OCZ for 18 months. Results: Combining OCZ with colchicine in MS+FMF patients significantly reduced the frequency of FMF attacks (p=0.003) and the frequency of joint attacks (p=0.002). Consistent with the clinical improvement, the maximum serum C-reactive protein levels were significantly decreased after combination therapy compared to before combination therapy (p=0.003). MS+FMF patients reported that FMF disease activity improved after OCZ therapy (Visual Analog Scale [VAS] 74±9.6 vs. VAS 46.5±8.1 mm, p=0.003). Conclusion: Ocrelizumab therapy led to a prominent decrease in the frequency of FMF attacks, alleviated functional impairment, and improved quality of life in MS+FMF patients.